Meta-analysis of the effect of plyometric training on the athletic performance of youth basketball players - Zhou, J.-Y.; Wang, X.; Hao, L.; Ran, X.-W.; Wei, W. (Frontiers in Physiology, 2024)
Objective: To investigate the effects of Plyometric Training (PT) on the athletic performance of youth basketball players (age 5-17.99) and to provide a theoretical basis for applying PT in basketball training practice.